Semiconductive shielding material and preparation method and application thereof
Through the preparation raw materials and process processing of specific ratios, the problem of excessive volume resistivity of existing semiconductor shielding materials under high voltage levels is solved, and the material's low resistivity, high mechanical properties and stable power supply effect are achieved, and it is suitable for high-voltage cable applications.
Patent Information
- Application Number
- CN202411580559.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing semiconductor shielding materials have too high volume resistivity under high voltage levels, making it difficult to meet the needs of high voltage cable materials.
The preparation raw materials with a specific ratio are adopted, including 59 parts to 63 parts of matrix resin, 34 parts to 38 parts of conductive carbon black, 1 part to 1.5 parts to 1.5 parts to crosslinking agent, 0.5 parts to 2 parts of dispersant, 0.5 parts to 3 parts of lubricant, 0.5 parts to 1.5 parts of antioxidant, and through a specific kneading and drying process, a semiconductor shielding material with excellent electrical and mechanical properties is formed.
It significantly reduces the volume resistivity of semiconductor shielding materials, improves tensile strength and elongation of break, suppresses the positive temperature resistance effect, ensures the stability of cable power supply, and is suitable for high-voltage cable shielding materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a semi-conductive shielding material and a preparation method and application thereof. Background Art
[0002] With the gradual depletion of global fossil energy and the continuous increase in human electricity demand, the world has vigorously developed the new energy industry and competed to develop new energy in the marine field. Cables are the only channel from offshore new energy to land. Under this trend, higher requirements are placed on the performance of cable materials, moving towards higher voltage levels and capacities. Correspondingly, higher requirements are also placed on the performance of cable shielding materials under high voltage levels. The current volume resistivity of semi-conductive shielding materials is too high to meet the demand for cable materials under high voltage levels. Summary of the invention
[0003] Based on this, it is necessary to provide a semi-conductive shielding material and a preparation method and application thereof, aiming to improve the volume resistivity of the semi-conductive shielding material.
[0004] In one aspect of the present application, a semiconductive shielding material is provided, wherein the raw materials for preparing the semiconductive shielding material include the following components in parts by weight: 59 to 63 parts of a base resin, 34 to 38 parts of conductive carbon black, 1 to 1.5 parts of a crosslinking agent, 0.5 to 2 parts of a dispersant, 0.5 to 3 parts of a lubricant, and 0.5 to 1.5 parts of an antioxidant;
[0005] The conductive carbon black has an iodine absorption value of >65 g / kg, an oil absorption value of ≥140 mL / 100 g, a compression oil absorption value of >90 mL / 100 g, a 325-mesh sieve residue of ≤10 ppm, and an ash content of <0.1%.
[0006] The raw materials for preparing the above-mentioned semi-conductive shielding material of the present application adopt specific raw material components and ratios, especially conductive carbon black with specific performance parameters is used as the conductive filler. Specifically, the iodine absorption value of the conductive carbon black is >65g / Kg, which ensures that the conductive carbon black has a larger specific surface area, so that it is easy to contact to form a network path, thereby improving the conductivity of the shielding material, and the path is not easily destroyed at high temperature, thereby suppressing the positive resistance effect; when the oil absorption value of the conductive carbon black is ≥140mL / 100g, the conductive carbon black itself has sufficient structural degree, thereby making it easier to form a conductive path; and the compressed oil absorption value of the conductive carbon black is >90mL / 100g, which ensures that the conductive carbon black still has a larger network structure during the mixing process; the ash content of the conductive carbon black is <0.1%, so as to ensure that the conductive carbon black is of higher purity, which is beneficial to electron migration and improves the inherent conductivity of the material. In this way, the semi-conductive shielding material has low volume resistivity, high tensile strength, high elongation at break, low PTC coefficient, excellent electrical and mechanical properties, and effectively suppresses the positive temperature resistance effect, which is beneficial to the stability of cable power supply, can meet the demand for cable materials under high voltage levels, and is suitable for the field of high-voltage cable shielding materials.
[0007] The raw materials used in the preparation of the semi-conductive shielding material of the present application adopt specific raw material components and ratios, which have a synergistic effect on the performance of the shielding material. The obtained semi-conductive shielding material has better electrical and mechanical properties, and effectively suppresses the positive temperature resistance effect, which is beneficial to the stability of the cable power supply.
[0008] In some embodiments, the conductive carbon black satisfies one or more of the following conditions:
[0009] (1) The iodine absorption value of the conductive carbon black is 72-100 g / kg;
[0010] (2) The oil absorption value of the conductive carbon black is 149-180 mL / 100 g;
[0011] (3) The compression oil absorption value of the conductive carbon black is 101~140mL / 100g;
[0012] (4) The 325 mesh sieve residue of the conductive carbon black is 4 to 8 ppm;
[0013] (5) The ash content of the conductive carbon black is 0.001% to 0.06%;
[0014] (6) The toluene transmittance of the conductive carbon black is ≥98%.
[0015] In some embodiments, the preparation raw materials are calculated by weight: the base resin is 61 to 63 parts, the conductive carbon black is 36 to 38 parts, the cross-linking agent is 1.2 to 1.5 parts, the dispersant is 1 to 2 parts, the lubricant is 2 to 3 parts, and the antioxidant is 1 to 1.5 parts.
[0016] In some embodiments, the semiconductive shielding material satisfies at least one of the following conditions (1) to (5):
[0017] (1) The melt index of the matrix resin is ≥6g / 10min;
[0018] (2) The elongation at break of the matrix resin is ≥700%;
[0019] (3) The matrix resin is ethylene-vinyl acetate, and the molar content of vinyl acetate in the ethylene-vinyl acetate is 17% to 28%;
[0020] (4) The base resin is ethylene-butyl acrylate, and the molar content of butyl acrylate in the ethylene-butyl acrylate is 10% to 28%;
[0021] (5) The matrix resin is ethylene-ethyl acrylate, and the molar content of ethyl acrylate in the ethylene-ethyl acrylate is 10% to 20%.
[0022] In some embodiments, the cross-linking agent is one or both of di-tert-butyl peroxyisopropylbenzene and diisopropylbenzene peroxide.
[0023] In some embodiments, the dispersant is one or both of 760W dispersant and ethylene bisstearamide.
[0024] In some embodiments, the lubricant is one or more of zinc stearate, PE cracking wax, silicone oil and microcrystalline wax.
[0025] In some embodiments, the antioxidant is one or more of antioxidant RD, antioxidant 300, antioxidant 168 and antioxidant 1010.
[0026] A second aspect of the present application provides a method for preparing the semiconductive shielding material as described in the first aspect, comprising the following steps:
[0027] S1, mixing the base resin, conductive carbon black, dispersant, lubricant and antioxidant according to the composition of the raw materials, and then preparing pellets;
[0028] S2, drying the pellets;
[0029] S3, adding a cross-linking agent to the dried granules for cross-linking agent absorption to obtain a semi-conductive shielding material.
[0030] In some embodiments, the method for preparing the semiconductive shielding material satisfies at least one of the following conditions (1) to (3):
[0031] (1) In step S1, the mixing temperature is 120° C. to 220° C.;
[0032] (2) In step S2, the pellets are dried to a moisture content of ≤200 ppm by weight;
[0033] (3) In the step S3, the cross-linking agent is added to the dried pellets at a temperature of 60° C. to 75° C.
[0034] The third aspect of the present application provides a semiconductive shielding product, comprising the semiconductive shielding material as described in the first aspect and the semiconductive shielding material prepared by the preparation method as described in the second aspect.
[0035] A fourth aspect of the present application provides a high-voltage cable, comprising the semi-conductive shielding material as described in the first aspect and the semi-conductive shielding material prepared by the preparation method as described in the second aspect.
[0036] A fifth aspect of the present application provides an electrical device comprising the high voltage cable as described in the fourth aspect. DETAILED DESCRIPTION
[0037] For ease of understanding of the present application, the present application will be described more fully below with reference to the relevant embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0039] Semi-conductive shielding materials are supporting materials for high-voltage and ultra-high-voltage cables. They are mainly used for the inner and outer shielding layers of high-voltage and ultra-high-voltage cables. They play the role of alleviating the electric field stress concentration inside the cable, uniformly distributing the electric field stress on the surface of the insulation layer, and shielding the electromagnetic radiation generated by the cable. Conductive filler is one of the key components of semi-conductive shielding materials, affecting important properties of semi-conductive shielding materials such as electrical, mechanical, thermal, processability, and surface finish. Conductive carbon black has become the main choice for conductive fillers in the production of semi-conductive shielding materials for high-voltage cables due to its good electrical properties and low cost. However, with the rapid development of the power industry, the power grid system is moving towards higher voltage levels and capacities, which puts higher requirements on transmission cables. Existing semi-conductive shielding materials are difficult to meet the requirements in terms of electrical properties.
[0040] Based on this, one embodiment of the present application provides a semiconductive shielding material, the raw materials for its preparation include the following components in parts by mass: 59 to 63 parts of base resin, 34 to 38 parts of conductive carbon black, 1 to 1.5 parts of crosslinking agent, 0.5 to 2 parts of dispersant, 0.5 to 3 parts of lubricant, and 0.5 to 1.5 parts of antioxidant;
[0041] The conductive carbon black has an iodine absorption value of >65 g / kg, an oil absorption value of ≥140 mL / 100 g, a compression oil absorption value of >90 mL / 100 g, a 325-mesh sieve residue of ≤10 ppm, and an ash content of <0.1%.
[0042] The conductive carbon black includes but is not limited to nano carbon black, furnace black and acetylene black.
[0043] The raw materials for preparing the above-mentioned semi-conductive shielding material of the present application adopt specific raw material components and ratios, especially conductive carbon black with specific performance parameters is used as the conductive filler. Specifically, the iodine absorption value of the conductive carbon black is >65g / Kg, which ensures that the conductive carbon black has a larger specific surface area, so that it is easy to contact to form a network path, thereby improving the conductivity of the shielding material, and the path is not easily destroyed at high temperature, thereby suppressing the positive resistance effect; when the oil absorption value of the conductive carbon black is ≥140mL / 100g, the conductive carbon black itself has sufficient structural degree, thereby making it easier to form a conductive path; and the compressed oil absorption value of the conductive carbon black is >90mL / 100g, which ensures that the conductive carbon black still has a larger network structure during the mixing process; the ash content of the conductive carbon black is <0.1%, so as to ensure that the conductive carbon black is of higher purity, which is beneficial to electron migration and improves the inherent conductivity of the material. In this way, the semi-conductive shielding material prepared using the raw material has low volume resistivity, high tensile strength, high elongation at break, low PTC coefficient, excellent electrical and mechanical properties, and effectively inhibits the positive temperature resistance effect, which is beneficial to the stability of cable power supply, can meet the demand for cable materials under high voltage levels, and is suitable for the field of high-voltage cable shielding materials.
[0044] Measurement method of iodine absorption value of conductive carbon black: iodine absorption value is measured according to GB / T 3780.1-2015.
[0045] Measurement method of oil absorption value of conductive carbon black: Oil absorption value is measured according to GB / T 3780.2-2017.
[0046] Measurement method of compression oil absorption value of conductive carbon black: Compression oil absorption value measurement is carried out according to GB / T 3780.4-2017.
[0047] Measurement method of 325 mesh sieve residue of conductive carbon black: 325 mesh sieve residue measurement is carried out according to GB / T 3780.21-2016.
[0048] The ash content of conductive carbon black is measured in accordance with GB / T 3780.10-2017.
[0049] As an example, the iodine absorption value of the conductive carbon black may be 66 g / kg, 67 g / kg, 68 g / kg, 69 g / kg, 70 g / kg, 71 g / kg, 72 g / kg, 73 g / kg, 74 g / kg, 75 g / kg, 76 g / kg, 77 g / kg, 78 g / kg, 79 g / kg, 80 g / kg, 81 g / kg, 82 g / kg, 83 g / kg, 84 g / kg, 85 g / kg, 86 g / kg, 87 g / kg, 88 g / kg, 89 g / kg, 90 g / kg, 91 g / kg, 92 g / kg, 93 g / kg, 94 g / kg, 95 g / kg, 96 g / kg, 97 g / kg, 98 g / kg, 99 g / kg, 100 g / kg, or it can be within the range formed by any two of the above point values as end values, such as 66g / kg~100g / kg. Furthermore, the iodine absorption value of the conductive carbon black is 72~100g / kg. The conductive carbon black with an iodine absorption value of 72~100g / kg is used to ensure that the conductive carbon black has a larger specific surface area, so that it is easy to contact to form a mesh path, thereby improving the conductivity of the shielding material; and the path is not easily destroyed at high temperatures, thereby suppressing the positive resistance effect, greatly reducing the increase in the volume resistivity of the shielding material with increasing temperature, so that the positive temperature coefficient (PTC) is within an acceptable range, ensuring that the shielding material can continue to work under high pressure.
[0050] As an example, the oil absorption value of the conductive carbon black can be 140 mL / 100g, 143 mL / 100g, 145 mL / 100g, 149 mL / 100g, 150 mL / 100g, 155 mL / 100g, 160 mL / 100g, 165 mL / 100g, 170 mL / 100g, 175 mL / 100g, 180 mL / 100g, or it can be within the range of any two of the above point values as end values, for example, 140 mL / 100g~180 mL / 100g. Further, the oil absorption value of the conductive carbon black is 149~180 mL / 100g. Using conductive carbon black with an oil absorption value of 149~180 mL / 100g is conducive to optimizing the internal structure of the shielding material and ultimately improving the conductive performance of the shielding material.
[0051] As an example, the compression oil absorption value of the conductive carbon black can be 91mL / 100g, 95mL / 100g, 100mL / 100g, 101mL / 100g, 105mL / 100g, 110mL / 100g, 115mL / 100g, 120mL / 100g, 125mL / 100g, 130mL / 100g, 135mL / 100g, 140mL / 100g, or it can be within the range formed by any two of the above point values as end values, such as 91mL / 100g~140mL / 100g. Further, the compression oil absorption value of the conductive carbon black is 101~140mL / 100g. Using the conductive carbon black with a compression oil absorption value of 101~140mL / 100g can ensure that the conductive carbon black still has a huge network structure during the mixing process, promote the formation of a mesh path, and thus improve the conductivity of the shielding material.
[0052] As an example, the 325-mesh residue of the conductive carbon black can be 0.5ppm, 1ppm, 2ppm, 3ppm, 4ppm, 5ppm, 6ppm, 7ppm, 8ppm, 9ppm, 10ppm, or can be within the range formed by any two of the above point values as end values, such as 0.5ppm~10ppm. Furthermore, the 325-mesh residue of the conductive carbon black is 4~8ppm. Using conductive carbon black with a residue of 4~8ppm, within this particle size range, the shielding material prepared not only has excellent electrical properties, but also greatly improved mechanical properties.
[0053] As an example, the ash content of the conductive carbon black can be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.099%, or can be within the range of any two of the above point values as end values, such as 0.001% to 0.099%. Furthermore, the ash content of the conductive carbon black is 0.001% to 0.06%. The conductive carbon black with an ash content of 0.001% to 0.06% is used, and the conductive carbon black has high purity, which is conducive to electron migration, improves the inherent conductivity of the conductive carbon black material, and ultimately improves the electrical properties of the shielding material.
[0054] In some embodiments, the toluene transmittance of the conductive carbon black is ≥98%. As an example, the toluene transmittance of the conductive carbon black can be 98%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, or it can be within the range of any two of the above point values as end values, such as 98%~99.9%. Further, the toluene transmittance of the conductive carbon black is 98%~99.5%. Conductive carbon black with a toluene transmittance of 98%~99.5% is used to improve the optical properties of the conductive carbon black, and ultimately the electrical and mechanical properties of the shielding material can meet the requirements, while the positive temperature coefficient PTC is within an acceptable range, and the resistance of the shielding material at high temperature will not increase rapidly, so that it can continue to work under high pressure.
[0055] In some of the embodiments, the conductive carbon black has an iodine absorption value of 72-100 g / kg, an oil absorption value of 149-180 mL / 100 g, a compressed oil absorption value of 101-140 mL / 100 g, a 325 mesh sieve residue of 4-8 ppm, an ash content of 0.001%-0.06%, and a toluene transmittance of 98%-99.5%. The semi-conductive shielding material is prepared by using specific raw material components and proportions, and in particular, conductive carbon black with specific performance parameters is used as the conductive filler. Specifically, the conductive carbon black has an iodine absorption value of 72-100 g / kg, an oil absorption value of 149-180 mL / 100 g, a compressed oil absorption value of 101-140 mL / 100 g, a 325-mesh sieve residue of 4-8 ppm, an ash content of 0.001%-0.06%, and a toluene transmittance of 98%-99.5%. The semi-conductive shielding material prepared by using these raw materials has low volume resistivity, high tensile strength, high elongation at break, and low PTC coefficient, has excellent electrical and mechanical properties, effectively suppresses the positive temperature resistance effect, is beneficial to the stability of cable power supply, can meet the demand for cable materials under high voltage levels, and is suitable for the field of high-voltage cable shielding materials.
[0056] In some of the embodiments, the mass fraction of the conductive carbon black is 34 to 38 parts. As an example, the mass fraction of the conductive carbon black can be 34, 35, 36, 37, and 38 parts, or it can be within the range of any two of the above point values as end values, and the mass fraction of the conductive carbon black is preferably 36 to 38 parts. If too much conductive filler is added, the rigidity of the blended material is too high, the flexibility becomes poor, and the purpose of high softness cannot be achieved. In addition, too much conductive filler will cause the surface of the material to be rough and not smooth, which will cause uneven electric field distribution and stress concentration in the cable insulation layer, and ultimately cause the risk of breakdown of the cable insulation layer; if too little conductive filler is added, the conductive effect of the semi-conductive shielding material of the present application cannot be achieved.
[0057] Conductive carbon blacks include, but are not limited to, nano carbon black, furnace black, and acetylene black. Carbon blacks with ash and sulfur contents less than or equal to 50 ppm are particularly suitable for cable applications because the asperities at the shield-insulation interface tend to increase local electrical stresses on the insulation, thereby shortening the service life of the cable. The actual size and number density of these asperities can be reduced by selecting appropriate manufacturing conditions or carbon blacks with appropriate morphology and cleaning properties, or both, thereby increasing cable life.
[0058] In some embodiments, the mass fraction of the matrix resin is 59 parts to 63 parts. As an example, the mass fraction of the matrix resin can be 59 parts, 60 parts, 61 parts, 62 parts, and 63 parts, or can be within the range formed by any two of the above point values as end values. The mass fraction of the matrix resin is preferably 61 parts to 63 parts.
[0059] In some embodiments, the mass fraction of the cross-linking agent is 1 to 1.5 parts. As an example, the mass fraction of the cross-linking agent can be 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, and 1.5 parts, or can be within the range of any two of the above points as end values. The mass fraction of the cross-linking agent is preferably 1.2 to 1.5 parts.
[0060] In some embodiments, the mass fraction of the dispersant is 0.5 to 2 parts. As an example, the mass fraction of the dispersant can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, and 2.0 parts, or can be within the range of any two of the above points as end values. The mass fraction of the dispersant is preferably 1 to 2 parts.
[0061] In some embodiments, the mass fraction of the lubricant is 0.5 to 3 parts. As an example, the mass fraction of the lubricant can be 0.5, 1.0, 1.5, 2.0, 2.5 and 3 parts, or can be within the range of any two of the above points as end values. The mass fraction of the lubricant is preferably 2 to 3 parts.
[0062] In some embodiments, the weight fraction of the antioxidant is 0.5 to 1.5 parts. As an example, the weight fraction of the antioxidant can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 and 1.5 parts, or can be within the range of any two of the above points as end values. The weight fraction of the antioxidant is preferably 1 to 1.5 parts.
[0063] In some of the embodiments, the preparation raw materials include the following components in parts by weight: 59 to 63 parts of base resin, 34 to 38 parts of conductive carbon black, 1 to 1.5 parts of cross-linking agent, 0.5 to 2 parts of dispersant, 0.5 to 3 parts of lubricant, and 0.5 to 1.5 parts of antioxidant.
[0064] Furthermore, the semiconductive shielding material comprises the following raw material components in parts by weight: 61 to 63 parts of base resin, 36 to 38 parts of conductive carbon black, 1.2 to 1.5 parts of crosslinking agent, 1 to 2 parts of dispersant, 2 to 3 parts of lubricant, and 1 to 1.5 parts of antioxidant.
[0065] In some embodiments, the melt index of the matrix resin is ≥6g / 10min. When the melt index of the resin is within this range, the viscosity and average molecular weight are suitable, which is conducive to improving the processing performance and fluidity of the matrix resin; the melt index of the matrix resin of the present application is measured according to ASTM D1238 standard at 190°C and with a test load of 21.6Kg.
[0066] In some embodiments, the elongation at break of the matrix resin is ≥700%, preferably ≥800%, and more preferably ≥900%.
[0067] In some embodiments, the base resin is ethylene vinyl acetate, and the molar content of vinyl acetate in the ethylene vinyl acetate is 17% to 28%.
[0068] In some of the embodiments, the base resin is ethylene-butyl acrylate, and the molar content of butyl acrylate in the ethylene-butyl acrylate is 10% to 28%.
[0069] In some of the embodiments, the base resin is ethylene-ethyl acrylate, and the molar content of ethyl acrylate in the ethylene-ethyl acrylate is 10% to 20%.
[0070] In some embodiments, the cross-linking agent is one or both of di-tert-butyl peroxyisopropylbenzene and diisopropylbenzene peroxide.
[0071] In some embodiments, the dispersant is one or both of 760W dispersant and ethylene bis stearamide. The 760W dispersant can be TEGO Dispers 760W dispersant.
[0072] In some of the embodiments, the lubricant is one or more of zinc stearate, PE cracking wax, silicone oil and microcrystalline wax.
[0073] In some of the embodiments, the antioxidant is one or more of antioxidant RD, antioxidant 300, antioxidant 168 and antioxidant 1010.
[0074] A second aspect of the present application provides a method for preparing the semiconductive shielding material as described in the first aspect, comprising the following steps:
[0075] S1, mixing the base resin, conductive carbon black, dispersant, lubricant and antioxidant according to the composition of the raw materials, and then preparing pellets;
[0076] S2, drying the pellets;
[0077] S3, adding a cross-linking agent to the dried granules for cross-linking agent absorption to obtain a semi-conductive shielding material.
[0078] In some embodiments, in S1, the mixing temperature is 120°C to 220°C, and pellets are obtained by pelletizing. As an example, the mixing temperature can be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C and 220°C, or can be within a range consisting of any two of the above point values as end values.
[0079] In some embodiments, in S2, the pellets are dried to a moisture content by weight ≤ 200 ppm; as an example, the moisture content by weight may be 200 ppm, 190 ppm, 180 ppm, 170 ppm, 160 ppm, 150 ppm, 140 ppm, 130 ppm, 120 ppm, 110 ppm, 100 ppm, or may be within a range consisting of any two of the above point values as end values.
[0080] In some embodiments, in S3, the cross-linking agent is added to the dried pellets at a temperature of 60° C. to 75° C., so that the cross-linking agent is completely and evenly absorbed.
[0081] In some embodiments, after the cross-linking agent is completely absorbed, the granules are added to a powder removal device for powder screening to remove the highly mixed powder to obtain the shielding material.
[0082] The third aspect of the present application provides a semiconductive shielding product, comprising the semiconductive shielding material as described in the first aspect and the semiconductive shielding material prepared by the preparation method as described in the second aspect.
[0083] Further, the semiconductive shielding product is a high voltage cable semiconductive shielding product. As an example, the semiconductive shielding product can be a semiconductive shielding sleeve.
[0084] The fourth aspect of the present application provides a high voltage cable, comprising the semiconductive shielding material as described in the first aspect and the semiconductive shielding material prepared by the preparation method as described in the second aspect. The semiconductive shielding material can be applied to the inner shielding layer material and the outer shielding layer material of the high voltage cable.
[0085] Furthermore, the high-voltage cable includes a conductor, an insulating layer and a semi-conductive shielding layer; the insulating layer is wrapped around the outer surface of the conductor, and the semi-conductive shielding layer is located on at least one of the two surfaces of the insulating layer facing the conductor and away from the conductor; at least one semi-conductive shielding layer is made of raw materials containing the semi-conductive shielding material of the present application.
[0086] In a specific example, both surfaces of the insulating layer facing the conductor and facing away from the conductor are provided with semi-conductive shielding layers. In this case, the cable includes a conductor, an inner shielding layer, an insulating layer and an outer shielding layer arranged in sequence from the inside to the outside. One or both of the inner shielding layer and the outer shielding layer are made of raw materials containing the semi-conductive shielding material of the present application.
[0087] A fifth aspect of the present application provides an electrical device comprising the high voltage cable as described in the fourth aspect.
[0088] The above-mentioned power-consuming devices may include, but are not limited to, high-voltage and large-capacity power system transmission devices, island power supply devices, offshore wind energy, tidal energy and other new energy development and utilization devices, etc.
[0089] In order to make the purpose, technical solutions and advantages of the present application more concise and clear, the present application is described with the following specific embodiments, but the present application is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present application and can be used to describe the present application, and cannot be understood as limiting the scope of the present application. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
[0090] In order to better illustrate the present application, the present application is further described below in conjunction with the embodiments. The following are specific embodiments.
[0091] Example 1
[0092] Ingredients: In this embodiment, the raw materials are: 59 parts of polyolefin resin, 38 parts of conductive filler, 0.5 parts of dispersant, 0.7 parts of lubricant, 0.8 parts of antioxidant and 1 part of crosslinking agent. The polyolefin resin is ethylene-butyl acrylate (EBA), and the melt index of ethylene-butyl acrylate (EBA) at 190°C and 21.6Kg is 7g / 10min, the elongation at break is 800%, and the density is 0.924g / cm 3 . The conductive filler is conductive carbon black, the iodine absorption value is 72g / Kg, the oil absorption value is 143ml / 100g, the compressed oil absorption value is 95 ml / 100g, the 325 mesh residue is 10ppm, the ash content is 0.06%, and the toluene transmittance is 98%. The dispersant is ethylene bis stearamide. The antioxidant is antioxidant RD. The lubricant is microcrystalline wax. The crosslinking agent is di-tert-butyl peroxyisopropylbenzene (BIBP);
[0093] Ethylene-butyl acrylate (EBA), conductive carbon black, crosslinking agent, dispersant, lubricant and antioxidant are weighed according to the above ratio;
[0094] Ethylene-butyl acrylate (EBA), conductive carbon black, dispersant, lubricant and antioxidant are fed into an extruder, kneaded at 200° C., and then pelletized to obtain pellets;
[0095] The pelletized material is placed in a drying device and dried to a moisture content of ≤200ppm;
[0096] Adding cross-linking agent: spray the dried pellets with liquefied cross-linking agent at 70°C and keep warm to ensure that the cross-linking agent is completely and evenly absorbed;
[0097] Powder removal: Add the granular material into the powder removal equipment for powder screening and removal of the highly mixed powder to obtain the semi-conductive shielding material, and then transport the prepared cable shielding material to the silo.
[0098] Example 2
[0099] The preparation method of Example 2 is basically the same as the preparation method of Example 1, except that: the iodine absorption value of the conductive carbon black is 71 g / kg, the oil absorption value is 149 ml / 100g, the compressed oil absorption value is 101 ml / 100g, the 325 mesh residue is 4 ppm, the ash content is 0.04%, and the toluene transmittance is 98%.
[0100] Example 3
[0101] The preparation method of Example 3 is substantially the same as that of Example 1, except that the iodine absorption value of the conductive carbon black is 100 g / kg.
[0102] Example 4
[0103] The preparation method of Example 4 is substantially the same as that of Example 1, except that the oil absorption value of the conductive carbon black is 180 mL / 100 g.
[0104] Example 5
[0105] The preparation method of Example 5 is substantially the same as that of Example 1, except that the compression oil absorption value of the conductive carbon black is 140 mL / 100 g.
[0106] Example 6
[0107] The preparation method of Example 6 is substantially the same as that of Example 1, except that the 325-mesh sieve residue of the conductive carbon black is 8 ppm.
[0108] Example 7
[0109] The preparation method of Example 7 is substantially the same as that of Example 1, except that the ash content of the conductive carbon black is 0.001% (ie, 10 ppm).
[0110] Example 8
[0111] The preparation method of Example 8 is substantially the same as that of Example 1, except that the toluene transmittance of the conductive carbon black is 99.5%.
[0112] Example 9
[0113] The preparation method of Example 9 is basically the same as the preparation method of Example 1, except that the raw material ratio is: 63 parts of ethylene-butyl acrylate, 34 parts of conductive carbon black, 2 parts of ethylene bisstearamide, 3 parts of microcrystalline wax, 1.5 parts of antioxidant RD and 1.5 parts of di-tert-butyl peroxyisopropylbenzene.
[0114] Example 10
[0115] The preparation method of Example 10 is basically the same as the preparation method of Example 1, except that: 61 parts of ethylene-butyl acrylate, 36 parts of conductive carbon black, 1 part of ethylene bisstearamide, 2 parts of microcrystalline wax, 1 part of antioxidant RD and 1.2 parts of di-tert-butyl peroxyisopropylbenzene.
[0116] Comparative Example 1
[0117] The preparation method of Comparative Example 1 is basically the same as the preparation method of Example 1, except that: the iodine absorption value of the conductive carbon black is 46 g / kg, the oil absorption value is 118 ml / 100g, the compressed oil absorption value is 85 ml / 100g, the 325 mesh residue is 8 ppm, the ash content is 0.12%, and the toluene transmittance is 99%.
[0118] Comparative Example 2
[0119] The preparation method of Comparative Example 2 is basically the same as that of Example 1, except that the iodine absorption value of the conductive carbon black is 43 g / kg, the oil absorption value is 110 ml / 100g, the compressed oil absorption value is 84 ml / 100g, the 325 mesh residue is 11 ppm, the ash content is 0.12%, and the toluene transmittance is 98%.
[0120] Comparative Example 3
[0121] The preparation method of Comparative Example 3 is basically the same as that of Example 1, except that the raw material ratio is 67 parts of base resin, 30 parts of conductive carbon black, 0.5 parts of dispersant, 0.7 parts of lubricant, 0.8 parts of antioxidant and 1 part of cross-linking agent.
[0122] Comparative Example 4
[0123] The preparation method of Comparative Example 4 is substantially the same as that of Example 1, except that the conductive carbon black has an oil absorption value of 112 ml / 100 g, an ash content of 0.2%, and a toluene transmittance of 98%.
[0124] The shielding materials obtained in each embodiment and each comparative example were pressed into plates to form test specimens. Then the test specimens were tested for tensile strength, elongation at break, volume resistivity at room temperature, volume resistivity at 90°C and PTC coefficient. Among them, the volume resistivity at 23°C and the volume resistivity at 90°C were measured according to the method specified in GB / T 3048.3-2007; the tensile strength and elongation at break were measured according to the method specified in GB / T 1040.3-2022; the PTC coefficient is the ratio of the volume resistivity at 90°C to the volume resistivity at 23°C measured according to the method specified in GB / T3048.3-2007. The test results are shown in Table 1.
[0125] Table 1
[0126]
[0127] The performance requirements for shielding materials for high-voltage cables in GB / T 18890.2-2015 are: tensile strength ≥12MPa, elongation at break ≥150, volume resistivity at 23℃ ≤100Ω·cm, volume resistivity at 90℃ ≤350.
[0128] It can be seen from the result data of Examples 1 to 10 in Table 1 that the shielding material obtained by using high-performance conductive carbon black in accordance with the above ratio and using the above preparation method meets the requirements of GB / T 18890.2-2015, and while the elongation at break is higher than 230%, the volume resistivity at 23°C is less than 13Ω·cm, and the volume resistivity at 90°C is less than 100Ω·cm. It can be seen that it has higher mechanical properties and lower volume resistivity, and the PTC coefficient is also lower.
[0129] Compared with the conductive carbon black used in Example 1, the conductive carbon black used in Comparative Examples 1 and 2 has lower iodine absorption value, oil absorption value and compression oil absorption value, and higher 325 mesh sieve residue and ash content. By comparing the data of Example 1 with Comparative Examples 1 and 2, it can be seen that when the performance of the conductive carbon black does not meet the conditions, the elongation at break of the shielding material decreases significantly, the volume resistivity increases sharply, and the PTC coefficient also increases.
[0130] Compared with Example 1, the conductive filling of Comparative Example 3 is lower, and its volume resistivity at 23°C and 90°C are significantly increased, and the PTC coefficient is higher. It can be seen that the conductive filling amount significantly affects the volume resistivity of the shielding material.
[0131] Compared with the conductive carbon black used in Example 1, the conductive carbon black used in Comparative Example 4 has a lower oil absorption value and a higher ash content. Its structure is low and it contains more impurities. Therefore, the chain structure of the conductive carbon black aggregates is not well developed, the probability of forming a network structure is reduced, the conductivity is poor, and the volume resistivity at 23°C and the volume resistivity at 90°C are both high.
Claims
1. A semi-conductive shielding material, characterized in that: The raw materials for its preparation include the following components in parts by weight: 59 to 63 parts of base resin, 34 to 38 parts of conductive carbon black, 1 to 1.5 parts of a crosslinking agent, 0.5 to 2 parts of a dispersant, 0.5 to 3 parts of a lubricant, and 0.5 to 1.5 parts of an antioxidant; The conductive carbon black has an iodine absorption value of 66-100 g / kg, an oil absorption value of 140-180 mL / 100 g, a compressed oil absorption value of 91-140 mL / 100 g, a 325 mesh sieve residue of ≤10 ppm, and an ash content of <0.1%; The base resin is ethylene-butyl acrylate copolymer, and the molar content of butyl acrylate in the ethylene-butyl acrylate copolymer is 10% to 28%; Or the base resin is ethylene-ethyl acrylate copolymer, and the molar content of ethyl acrylate in the ethylene-ethyl acrylate copolymer is 10% to 20%.
2. The semiconductive shielding material according to claim 1, characterized in that The conductive carbon black satisfies one or more of the following conditions: (1) The iodine absorption value of the conductive carbon black is 72-100 g / kg; (2) The oil absorption value of the conductive carbon black is 149-180 mL / 100 g; (3) The compression oil absorption value of the conductive carbon black is 101~140mL / 100g; (4) The 325 mesh sieve residue of the conductive carbon black is 4 to 8 ppm; (5) The ash content of the conductive carbon black is 0.001% to 0.06%; (6) The toluene transmittance of the conductive carbon black is ≥98%.
3. The semiconductive shielding material according to claim 1, characterized in that In the preparation raw materials, by mass, the base resin is 61 to 63 parts, the conductive carbon black is 36 to 38 parts, the cross-linking agent is 1.2 to 1.5 parts, the dispersant is 1 to 2 parts, the lubricant is 2 to 3 parts, and the antioxidant is 1 to 1.5 parts.
4. The semiconductive shielding material according to claim 1, characterized in that Satisfy at least one of the following conditions (1) to (2): (1) The melt index of the matrix resin is ≥6g / 10min; (2) The elongation at break of the matrix resin is ≥700%.
5. The semiconductive shielding material according to any one of claims 1 to 4, characterized in that: The cross-linking agent is one or both of di-tert-butyl peroxyisopropylbenzene and diisopropylbenzene peroxide.
6. The semiconductive shielding material according to any one of claims 1 to 4, characterized in that: The dispersant is one or both of 760W dispersant and ethylene bisstearamide.
7. The semiconductive shielding material according to any one of claims 1 to 4, characterized in that: The lubricant is one or more of zinc stearate, PE cracking wax, silicone oil and microcrystalline wax.
8. The semiconductive shielding material according to any one of claims 1 to 4, characterized in that: The antioxidant is one or more of antioxidant RD, antioxidant 300, antioxidant 168 and antioxidant 1010.
9. A method for preparing a semiconductive shielding material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing the base resin, conductive carbon black, dispersant, lubricant and antioxidant according to the composition of the raw materials, and then preparing pellets; S2, drying the pellets; S3, adding a cross-linking agent to the dried granules for cross-linking agent absorption to obtain a semi-conductive shielding material.
10. The method for preparing a semiconductive shielding material according to claim 9, characterized in that: Satisfy at least one of the following conditions (1) to (3): (1) In S1, the mixing temperature is 120°C to 220°C; (2) In S2, the pellets are dried to a moisture content of ≤200 ppm by weight; (3) In S3, the cross-linking agent is added to the dried pellets at a temperature of 60° C. to 75° C.
11. A semiconductive shielding product, characterized in that: The invention comprises the semiconductive shielding material as described in any one of claims 1 to 8 or the semiconductive shielding material prepared by the preparation method as described in claim 9 or 10.
12. A high voltage cable, characterized in that: The invention comprises the semiconductive shielding material as described in any one of claims 1 to 8 or the semiconductive shielding material prepared by the preparation method as described in claim 9 or 10.
13. An electrical device, characterized in that: Comprising the high voltage cable as claimed in claim 12.
Citation Information
Patent Citations
Internal shielding material composition applied to cross-linked polyethylene cable and preparation method of composition
CN104419055A
Carbon black, electrically conductive resin composition, and electrode mixture
CN105283514A
Shield material used for cable with direct current of 500 kV and below as well as production method thereof
CN107488295A